1988
DOI: 10.1002/1097-0142(19880115)61:2<309::aid-cncr2820610221>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of histologic and clinical factors in 56 patients with gastrointestinal lymphomas

Abstract: To investigate the prognostic value of histologic and clinical factors in lymphomas of the gastrointestinal (GI) tract, the clinicopathologic findings in 56 Japanese patients with GI lymphomas were reviewed. They included 37 patients with gastric and 19 with intestinal lymphomas. The male to female ratio was 2.7:1 in gastric and 11:1 in small intestinal lymphomas. Histologically, all but one of intestinal lymphomas were high-grade lymphomas. Gastric lymphomas comprised 47% of low-grade and 53% of high-grade tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1
6

Year Published

1989
1989
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 21 publications
5
24
1
6
Order By: Relevance
“…Similar results were demonstrated in two previous studies. 12,19 Chronologic periods significantly influenced OS, but not EFS in our study. Weingrad et al 9 showed a similar time trend toward a better survival in the latest than the earliest period.…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…Similar results were demonstrated in two previous studies. 12,19 Chronologic periods significantly influenced OS, but not EFS in our study. Weingrad et al 9 showed a similar time trend toward a better survival in the latest than the earliest period.…”
Section: Discussioncontrasting
confidence: 42%
“…To our knowledge, 11 English studies performed a mul- tivariate analysis for prognostic factors on patients with both gastric and intestinal lymphoma. 9,[11][12][13][14][15][16]18,19,22,24 All but one 15 demonstrated an early stage to be the most significant prognostic factor for better survival. 9,[11][12][13][14]16,18,19,22,24 The next most frequent independent prognostic factor was a younger age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations